Pesticide use and cholinesterase inhibition in small-scale agricultural workers in southern Brazil - Samuel Botião Nerilo; Fernanda Andrade Martins; Luciana Botião Nerilo; Valter Eduardo Cocco Salvadego; Renan Yoshio Endo; Gustavo Henrique Oliveira Rocha; Simone Aparecida Galerani Mossini; Vanderly Janeiro; Paula Nishiyama; Miguel Machinski Junior (Universidade de São Paulo, 2014)
A controlled cross-sectional study of family growers of fruit and vegetables was conducted between October 2009 and October 2010 to characterize the use of pesticides, establish the socio-demographic profile, and analyze cholinesterase activity in small-scale agricultural workers in Southern Brazil. Data was collected for 173 workers and 179 controls. A structured questionnaire was applied collecting socio-demographic information and determining knowledge and work practices in relation to pesticide use. The benchmarks for total cholinesterase (ChEs) and butyrylcholinesterase (BuChE) were obtained from the average enzymatic activity of the occupationally unexposed group (control). The mean age of the exposed population was 40.0 ± 11.2 years. The symptoms differed significantly (p<0.05) between the exposed and unexposed populations. Forty (23.1%) workers showed symptoms associated with exposure to pesticides. The average value of enzymatic activity in the occupationally unexposed group for ChEs was 6.3 μmol/mL/min among males and 5.6 μmol/mL/min among females while for BuChE was 2.4 μmol/mL/min among males and 2.0 μmol/mL/min among females. Eight (4.6%) workers had high inhibition (>30%) of ChEs activity, whereas no workers showed high inhibition (>50%) of BuChE. Potential factors involved include gender, education, pesticide orientation, exposure, and hygiene measures.